Medical Documentation Practice of Health Professionals and Attitude towards it at University of Gondar Hospital, Gondar, North West Ethiopia - Adinew Belay; Y. Narasimha Rao (Institute of Advanced Engineering and Science, 2016)
Medical documentation is believed as pertinent facts of medicalcare plan. It is a warehouse for patient’s information and interaction with theircaregivers in particular. However, there are lack of completeness, consistency,proper recoding and other constraints regarding the current medical recordpractice. The main objective of this study was to assess the current medicaldocumentation practice of health professionals and attitude towards it atUniversity of Gondar Hospital, Gondar, North West Ethiopia, 2016.Institution based cross sectional quantitative study was conductedfrom March 15 to April 30, 2016 at University of Gondar Hospital. About 260health professionals who work in different wards were participated. Data werecollected using structured self-administered questionnaires of professionals andreviewed their recorded medical documentation (chart). Logistic regressions;both bi-variable and multi-variable logistic regressions analyses models werefitted. The odds ratio with 95 % CI was computed and these variables which havea (p-value < 0.05) in the multi-variable logistic regression analysis model weretaken as statistically significant and interpreted accordingly. Good medical documentation practice by health professionals was 45.4% (n=118). Documentation for all patients using documentation standard toolswith AOR=1.799(95%CI [1.065, 3.040]), working area with AOR=2.522(95%CI[1.264, 5.033]), and favourable attitude towards medical documentation withadjusted OR=1.182(95% CI [1.039, 3.169]) were significantly associated withgood medical documentation practice.Medical documentation practice at University of Gondar Hospital was found low.Documentation using standard tools, working area (setting) and attitude ofprofessionals were important factors associated with medical documentationpractice. Organizational support needs to be strengthening, ensure procedure,format and documentation type (including documentation tools and forms); etcneeds emphasis to improve documentation practice.